(untitled) (Research, Society and Development, 2020)
This work aimed to evaluate the level of perception that students of elementary school II have about various environmental issues and to show the main challenges that the school has to present this theme to the student. To conduct the research, questionnaires were applied in two schools in the municipality of Crato-CE, for students of elementary school II. Questions were asked related to various topics on environmental problems. The applied questions had the purpose of perceiving the differences in the answers, from the levels of the series attended by the interviewed students, on the subjects approached. The results obtained from a detailed analysis of the responses given by the interviewed students showed that the majority of students (approximately 90%) have a good awareness of environmental problems, even in the initial grades of elementary school II. However, it was also observed that as students move from the initial grades to the final grades, they demonstrate to acquire a better conception of some themes related to the environment. The students’ perception of environmental themes shows that they have been taught earlier on this type of subject. Such instructions are often made by sources other than the school. In this way, it is perceived that the school increasingly has a fundamental role in leading students to become aware citizens regarding the preservation of nature and the inclusion of environmental education in school curricula will contribute to this.